Development, Education and Learning Disability in India - Kalyanpur, Maya. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"This insightful book offers a critical discussion of disability and education in India that highlights the historical, political, sociocultural, economic, ideological and other local and global factors that shape inclusion and exclusion in this vast multilingual and multicultural global South country. Underpinned by a colonial/post-colonial and disability studies theoretical framework and based on a study conducted in 6 Mumbai schools, the book illustrates the complex intersections that create and perpetuate disadvantage, marginalisation and exclusion in the Indian context, as well as the role of discourses and practices uncritically imported from the North. The author's particular position as an insider/outsider in relation to the Indian context gives the book a unique lens, which sheds light on the tensions of translating global education agendas into local contexts. Written in an engaging and accessible style, this book is a must-read for anyone interested in inclusive education development, the intersections between disability and other forms of disadvantage, decolonising methodologies and social justice." - Dr Leda Kamenopoulou, Senior Lecturer in Special and Inclusive Education, School of Education, University of Roehampton, UK. This book uses qualitative research methods to examine why students in an Indian context are being identified as having learning disabilities on criteria that are largely drawn from the context of the Global North. It explores the push towards English language instruction as a possible factor that affects poor academic outcomes for students from low-income backgrounds who may be first-generation learners or English language learners. The book contrasts the different outcomes and supports for academically struggling students across low-income and middle-income backgrounds, with evidence to suggest that, despite the inclusionary principles of Education For All, this label is creating a marginalized group of students. Maya Kalyanpur is Professor at the Department of Learning and Teaching, University of San Diego, USA.
Chapter 1. The Indian Context -- Chapter 2. The Context for Inclusive Education -- Chapter 3. Policies in India -- Chapter 4. Social Hierarchies in the School -- Chapter 5. Language and Learning in the Classroom -- Chapter 6. Assessing for Learning Disabilities -- Chapter 7. Conclusion.
Keywords: Economic development; Biotechnology; Education and state; Development Studies; Development Studies; Development Studies; Biotechnology; Educational Policy and Politics